Characterization of anticancer, antimicrobial, antioxidant properties and chemical compositions of peperomia pellucida leaf extract - Lee Seong Wei; Wendy Wee (2011)
Peperomia pellucida leaf extract was characterized for its anticancer, antimicrobial, antioxidant activities, and chemical compositions. Anticancer activity of P. pellucida leaf extract was determined through Colorimetric MTT (tetrazolium) assay against human breast adenocarcinoma (MCF-7) cell line and the antimicrobial property of the plant extract was revealed by using two-fold broth micro-dilution method against 10 bacterial isolates. Antioxidant activity of the plant extract was then characterized using α, α- diphenyl-β-picrylhydrazyl (DPPH) radical scavenging method and the chemical compositions were screened and identified using gas chromatography-mass spectrometry (GC-MS). The results of present study indicated that P. pellucida leaf extract possessed anticancer activities with half maximal inhibitory concentration (IC50) of 10.4±0.06 μg/ml. The minimum inhibitory concentration (MIC) values were ranged from 31.25 to 125 mg/l in which the plant extract was found to inhibit the growth of Edwardsiella tarda, Escherichia coli, Flavobacterium sp., Pseudomonas aeruginosa and Vibrio cholerae at 31.25 mg/l; Klebsiella sp., Aeromonas hydrophila and Vibrio alginolyticus at 62.5 mg/l; and it was able to control the growth of Salmonella sp. and Vibrio parahaemolyticus at 125 mg/l. At the concentration of 0.625 ppt, the plant extract was found to inhibit 30% of DPPH, free radical. Phytol (37.88%) was the major compound in the plant extract followed by 2- Naphthalenol, decahydro- (26.20%), Hexadecanoic acid, methyl ester (18.31%) and 9,12-Octadecadienoic acid (Z,Z)-, methyl ester (17.61%). Findings from this study indicated that methanol extract of P. pellucida leaf possessed vast potential as medicinal drug especially in breast cancer treatment.